Biophysical screening in fragment-based drug design: a brief overview. (6th February 2019) - Robson-Tull, Jacob
Abstract: High-throughput screening (HTS) has been firmly rooted at the heart of many drug discovery programs over the past few decades, having provided a starting point for the development of many of the drugs on the market. However, this technique is often accompanied by high-attrition rates and has proven to be unsuccessful at developing therapeutics against more non-conventional targets such as protein–protein interactions (PPIs). Fragment-based drug discovery (FBDD) offers an alternative approach and is steadily being taken up by the industry to tackle the high-attrition rate associated with many chemical leads developed by HTS. FBDD takes a structure-guided approach and uses a small chemical library of fragments during the initial screening process, to identify weakly binding ligands with the potential for therapeutic development. This review aims to summarise the challenges with screening in FBDD and the key biophysical screening techniques used for identification of weakly interacting ligands.